2008
DOI: 10.1111/j.1467-9280.2008.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Relative Pitch Specific to Pitch?

Abstract: Melodies, speech, and other stimuli that vary in pitch are processed largely in terms of the relative pitch differences between sounds. Relative representations permit recognition of pitch patterns despite variations in overall pitch level between instruments or speakers. A key component of relative pitch is the sequence of pitch increases and decreases from note to note, known as the melodic contour. Here we report that contour representations are also produced by patterns in loudness and brightness (an aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 24 publications
(28 reference statements)
7
87
1
Order By: Relevance
“…On the other hand, CI users had significantly better contour identification with consistent pitch and loudness cues than with either cues alone. McDermott et al (2008) found that, with the relative sizes of intervals preserved, pitch and loudness changes in the same directions elicited common contour representations that were recognized across the two dimensions by NH listeners. Our results suggest that when pitch and loudness changed together, their common contour representations may be integrated to enhance contour identification with CIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, CI users had significantly better contour identification with consistent pitch and loudness cues than with either cues alone. McDermott et al (2008) found that, with the relative sizes of intervals preserved, pitch and loudness changes in the same directions elicited common contour representations that were recognized across the two dimensions by NH listeners. Our results suggest that when pitch and loudness changed together, their common contour representations may be integrated to enhance contour identification with CIs.…”
Section: Discussionmentioning
confidence: 99%
“…NH listeners can reliably identify contours across the pitch and loudness dimensions, as long as the directions and relative sizes of the changes across notes are similar in both dimensions (i.e., higher pitches mapped to louder sounds and vice versa). Such loudness cues can also be used to recognize familiar melodies, although the recognition accuracy is poorer than that with pitch cues (McDermott et al, 2008). Using dichotic listening tests, Neuhoff et al (1999) showed that pitch and loudness contour cues may interact with each other centrally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability appears effortless to humans: It is present in infancy and is a universal of human music cognition (25)(26)(27). In fact, the human ability to use relationships between acoustic cues to recognize sound sequences appears to extend beyond pitch, including loudness and perceptual brightness (28). In contrast, multiple studies over the past three decades indicate that songbirds lack relational pitch processing for tone sequences (22,29,30; but see refs.…”
mentioning
confidence: 95%
“…For instance, McDermott et al (2008) showed that listeners recognized transposed timbral brightness (and loudness) patterns in similar ways compared to pitch patterns, which indicates that relative representations, commonly thought of as a hallmark feature of pitch, could be a general feature of the auditory system. Also testing auditory sequence discrimination, Cousineau et al (2013) found strong commonalities between pitch and brightness processing for sequences of varying length, but distinct patterns of results for loudness.…”
Section: Introductionmentioning
confidence: 99%